Pendampingan Penyusunan Evaluasi Kompetensi Minimum (AKM) Pada SD Tangwala Skow Yambe Distrik Muara Tami Kota Jayapura - chelsi yuliana s.; Aisyah Ali; Sukmawati; Mamberuman M. Inggamer; Alam Anugrah (J-Abdimas Cenderawasih, 2023)
This Community Service Activity is carried out to help teachers in creating hot questions in preparing students who will take the Minimum Competency Assessment. In elementary school arithmetic, AKM wants to know to what extent students are able to understand and master basic mathematical concepts. However, in practice, there are still many schools that have not been able to implement AKM well due to a lack of understanding and knowledge about effective measurement methods. The method steps (1) Identify the problem. (2) Program design for the planned community service program. (3) Implementation of the program through various activities such as: Training and mentoring for school teachers, development of teaching materials and activities to motivate students. (4) This evaluation determines the extent to which this community service program can increase the introduction of AKM numeracy in elementary schools and students' ability to understand and master basic mathematical concepts. The results of the service are  improvements in numeracy and problem solving skills in AKM in elementary schools, students' ability to understand and master basic mathematical concepts, as well as students' interest and motivation to study numeracy topics